2019
DOI: 10.15640/ijn.v6n1a2
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence in Nurses and Emerging Trends: An Integrative Literature Review

Abstract: Aim: Determine the status of nursing literature regarding Emotional Intelligence. Background: Nurses work in emotionally charged environments, serving as frontline healthcare workers. Emotional Intelligence, a construct that emphasizes the evaluation and use of emotions, may be a valuable tool in the field of nursing. Method: A systematic literature review of the research on Emotional Intelligence, published between 2010 and 2017, in the nursing field was conducted. Results: 34 manuscripts were identified. A w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Additionally, (12) indicated that emotionally intelligent nurse managers are effective in managing conflict in the workplace whilst (24), revealed that interpersonal awareness of nurse managers ensures effective nursing leadership by recognising staff strengths and capabilities which are ways of determining how emotions manifest among nursing managers, and these related well with the reports of this present study. Moreover (25), found that nurse managers manifest emotions by demonstrating their ability to handle conflict-related challenges in the working environment, making them good managers at detecting the emotions of team members and as such able to motivate them to achieve organisational objective and findings correlated well with present study report.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, (12) indicated that emotionally intelligent nurse managers are effective in managing conflict in the workplace whilst (24), revealed that interpersonal awareness of nurse managers ensures effective nursing leadership by recognising staff strengths and capabilities which are ways of determining how emotions manifest among nursing managers, and these related well with the reports of this present study. Moreover (25), found that nurse managers manifest emotions by demonstrating their ability to handle conflict-related challenges in the working environment, making them good managers at detecting the emotions of team members and as such able to motivate them to achieve organisational objective and findings correlated well with present study report.…”
Section: Discussionsupporting
confidence: 70%
“…This indicates that irrespective of a nurse manager's emotional intelligence, their leadership skills is very paramount to attaining the set objectives of an organization (22). The outcome of a cross-sectional study conducted in Spain by (23) found that emotionally intelligent nurse managers facilitate the easy completion of tasks whilst considering their leadership styles. The study further denoted that, nurse managers demonstrated a significant correlation of their emotional intelligence to their leadership styles, therefore being effective in service delivery, hence outcome relating very well with present findings.…”
Section: Discussionmentioning
confidence: 99%